Stress and Growth in Cancer: Mechanisms and Psychotherapeutic Interventions to Facilitate a Constructive Balance - Cristian Ochoa Arnedo; Cristian Ochoa Arnedo; Cristian Ochoa Arnedo; Nuria Sánchez; Enric C. Sumalla; Anna Casellas-Grau; Anna Casellas-Grau (Frontiers in Psychology, 2019)
Post-traumatic stress and growth are common responses to adverse life events such as cancer. In this article, we establish how cancer becomes a “fertile land” for the emergence of stress and growth responses and analyze the main mechanisms involved. Stress-growth responses on adjusting to cancer is potentially determined by factors like the phase of the illness (e.g., initial phases vs. period of survivorship), patient’s coping strategies, meaning-making, and relationships with significant others. We also review the mechanisms of constructive and adaptative stress-growth balances in cancer to study the predictors, interrelated associations, triggering mechanisms, long-term results, and specific trajectories of these two responses to cancer. Finally, we update the evidence on the role of these stress-growth associations in psychologically adjusting to cancer. Together with this evidence, we summarize preliminary results regarding the efficacy of psychotherapeutic interventions that aim to facilitate a constructive psychological balance between stress and growth in cancer patients. Recommendations for future research and gaps in knowledge on stress-growth processes in this illness are also highlighted. Researchers are encouraged to design and use psychotherapeutic interventions according to the dynamic and changeable patients’ sources of stress and growth along the illness. Relevant insights are proposed to understand the inconsistency of stress-growth literature and to promote psychotherapeutic interventions to facilitate a constructive balance between these key responses in cancer.